A randomized prospective controlled trial comparing the laryngeal tube suction disposable and the supreme laryngeal mask airway: the influence of head and neck position on oropharyngeal seal pressure. Issue 1 (December 2015) - Somri, Mostafa; Vaida, Sonia; Fornari, Gustavo; Mendoza, Gabriela; Charco-Mora, Pedro; Hawash, Naser; Matter, Ibrahim; Swaid, Forat; Gaitini, Luis
Abstract Background The Laryngeal Tube Suction Disposable (LTS-D) and the Supreme Laryngeal Mask Airway (SLMA) are second generation supraglottic airway devices (SADs) with an added channel to allow gastric drainage. We studied the efficacy of these devices when using pressure controlled mechanical ventilation during general anesthesia for short and medium duration surgical procedures and compared the oropharyngeal seal pressure in different head and-neck positions. Methods Eighty patients in each group had either LTS-D or SLMA for airway management. The patients were recruited in two different institutions. Primary outcome variables were the oropharyngeal seal pressures in neutral, flexion, extension, right and left head-neck position. Secondary outcome variables were time to achieve an effective airway, ease of insertion, number of attempts, maneuvers necessary during insertion, ventilatory parameters, success of gastric tube insertion and incidence of complications. Results The oropharyngeal seal pressure achieved with the LTS-D was higher than the SLMA in, (extension (p =0.0150) and right position (p =0.0268﻿﻿ at 60 cm H2 O intracuff pressures and nearly significant in neutral position (p  = 0.0571). The oropharyngeal seal pressure was significantly higher with the LTS-D during neck extension as compared to SLMA (p = 0.015). Similar oropharyngeal seal pressures were detected in all other positions with each device. The secondary outcomes were comparable between both groups. Patients ventilated with LTS-D had higher incidence of sore throat (p  = 0.527). No major complications occurred. Conclusions Better oropharyngeal seal pressure was achieved with the LTS-D in head-neck right and extension positions , although it did not appear to have significance in alteration of management using pressure control mechanical ventilation in neutral position. The fiberoptic view was better with the SLMA. The post-operative sore throat incidence was higher in the LTS-D. Trial registration ClinicalTrials.gov ID:NCT02856672, Unique Protocol ID:BnaiZionMC-16-LG-001, Registered: August 2016.